Autologous Stem Cell Transplant in Hodgkin’s and Non-Hodgkin’s Lymphoma, Multiple Myeloma, and AL Amyloidosis - Sulaiman Mohammed Alnasser; Khalid Saad Alharbi; Ali F. Almutairy; Sulaiman Mohammed Almutairi; Abdulmalik Mohammed Alolayan (Cells, 2023)
Human body cells are stem cell (SC) derivatives originating from bone marrow. Their special characteristics include their capacity to support the formation and self-repair of the cells. Cancer cells multiply uncontrollably and invade healthy tissues, making stem cell transplants a viable option for cancer patients undergoing high-dose chemotherapy (HDC). When chemotherapy is used at very high doses to eradicate all cancer cells from aggressive tumors, blood-forming cells and leukocytes are either completely or partially destroyed. Autologous stem cell transplantation (ASCT) is necessary for patients in those circumstances. The patients who undergo autologous transplants receive their own stem cells (SCs). The transplanted stem cells first come into contact with the bone marrow and then undergo engraftment, before differentiating into blood cells. ASCT is one of the most significant and innovative strategies for treating diseases. Here we focus on the treatment of Hodgkin’s lymphoma, non-Hodgkin’s lymphoma, multiple myeloma, and AL amyloidosis, using ASCT. This review provides a comprehensive picture of the effectiveness and the safety of ASCT as a therapeutic approach for these diseases, based on the currently available evidence.